Handbook on globalization and higher education - King, Roger; Marginson, Simon 1951-; Naidoo, Rajani (Cheltenham, UK Edward Elgar, 2011)
This highly illuminating Handbook explores worldwide convergences and divergences in national higher education systems resulting from increased global co-operation and competition.
Includes bibliographical references and index.
Keywords: Education and globalization; Higher education and state